Clinical Experience of Use of High-dose Intravenous Methylprednisolone in Children With Acute Moderate to Severe Colitis. Issue 1 (July 2016) - Vora, Rakesh; Finnamore, Helen E.; Crook, Kay; Baillie, Colin; Whittle, Emma; Krishnamurthy, Balaji; Venkatesh, Krishnappa; Auth, Marcus K.H.
ABSTRACT: Objectives: Treatment of acute severe colitis (ASC) has been associated with high morbidity and high colectomy rate in children. In the prebiologics era, our centre used short-term high-dose intravenous corticosteroids (IVCS) at 2 to 30 mg · kg −1 · day −1 . We conducted a retrospective review to compare efficacy of different dosing regimes of IVCS. Methods: Thirty-four children treated with IVCS for ASC were included over 8 years. Patients were studied as 2 groups with similar pretreatment patient characteristics. Group 1 (standard dose) received IVCS at 2 mg · kg −1 · day −1 and group 2 (high dose) received IVCS at 10 to 30 mg · kg −1 · day −1 . Safety, efficacy, and follow-up of the entire cohort for >1 year were studied. The median IVCS dose in the standard- and high-dose cohort was 1.5 mg · kg −1 · day −1 (maximum 60 mg · kg −1 · day −1 ) and 24.8 mg · kg −1 · day −1 (maximum 1000 mg · kg −1 · day −1 ), respectively. Results: Pediatric Ulcerative Colitis Activity Index scores at day 5 were significantly lower in high-dose (15, interquartile range 8.5–20) than in standard-dose IVCS (30, interquartile range 20–30). IVCS side effects were minor and reversible. Overall, medical salvage therapy was required in 5.8% (2 children) before discharge, and in 17% (6 children) at follow-up after 1 year. The colectomy rate of the entire cohort was remarkably low with 0% during admission and 11% (4 children) after 1 year, with a trend of less colectomies in high-dose (4.8%—1 child) than in standard-dose (23%—3 children). Conclusions: Our data show that in paediatric ASC, the short-term use of high-dose IVCS is safe and effective. Prospective studies are needed to define the role of IVCS within salvage therapy protocols.